Focus on Primary Geography - Catling, Simon; Bagoly-Simó, Péter (Journal of Geography Education, 2022)
Primary Geography is crucial for our subject in so many ways. Material and imagined spaces and places shape young children's realities from an early age onwards and engage them with structures and processes in and of their natural, built, and human environment. It is these early years that can spark curiosity and motivation to understand how our world works in spatial and environmental terms and, most importantly, how each human being both individually and as a member of a community, can engage with it.